Statistical methods in determination of reference flow - Almeida, Isabel Kaufmann de; Alves Sobrinho, Teodorico; Santos, Bruno Bernardo dos; Steffen, Jorge Luiz; Bacchi, Cláudia Gonçalves Vianna (Comunicata Scientiae, 2014)
In this study we aimed to provide the foundation studies of water availability in the Miranda riverbasin, Mato Grosso do Sul, Brazil. Therefore, this study aimed to analyze the application of Normal,Log-Normal, Weibull, Gumbel and Log-Gumbel theoretical probability methods to data of minimumflows for seven consecutive days of the basin. To verify the adherence to the estimated probabilitiesof observed frequencies, we applied the Kolmogorov-Smirnov test. The results show that the Log-Gumbel distribution show greater accuracy in the data representation of the series and reach thebest fit value of Q7,10.